How Do In –Service English Teachers Enact Classroom Management Strategies in EFL Context? - Kardi Nurhadi; Devi Nur Afrilia (English Didactic, 2020)
Despite myriad of studies explore how the teachers enacting classroom management, there is a scant from the literature on investigating how the EFL teachers experiences while they were engaging classroom management. To fill this gap, this study report the teachers lived experiences in classroom management situated in EFL classroom. Grounded in qualitative approach narrative inquiry design, this research provided critical incidents or moments engaging in classroom management. Three English teachers participate voluntarily in this study. Data were derived from semi structure interview to capture the teachers lived experiences enacting classroom management. Drawing on the thematic analysis, three emergent findings are reported here.  First, the participants showed that the importance of classroom management strategies in EFL context, and they told about the main goals of classroom management strategies Second, the conditions.  It means there are some difficulties in the classroom management but the most of difficulties in manage the classroom are vocabularies, environment, and overactive students. The researchers asked the teachers' feelings when they are teaching in the classroom Third, strategies, the researcher found there are some strategies to manage the classroom such as organizing the physical design of the classroom, establishing rules and routines, developing caring relationships, implementing engaging and effective instruction, and addressing discipline issue.